Now I am a Teacher with My Way…: Integrated Happiness Pedagogy for Students’ Wellbeing - Satyal, Shrijana (NPRC Journal of Multidisciplinary Research, 2025)
This study outlines the origination of a unique pedagogical approach termed as “Happiness-Focused Dialogical Phenomenology”. This approach integrates elements of Constructivism and Transformative Learning Theory to create a holistic and transformative educational environment. Reflecting on the journey of a teacher, the study seeks to move beyond traditional teaching methods to foster a learning experience that prioritizes both academic rigor and student’s well-being. Drawing on the concept of signature pedagogy introduced by Lee S. Shulman (2005), it emphasizes the importance of creating a methodology that is both distinctive and effective in nurturing critical thinking, collaboration, and happiness among students. The proposed pedagogy is rooted in Constructivism, which posits that learners actively construct knowledge through experiences and social interactions, and Transformative Learning Theory, which focuses on perspectives that transform through disorienting dilemmas and critical reflection. The study combines these theories with dialogue-based learning and portfolio assessments to encourage students to reflect on their experiences, engage in meaningful discussions and develop a deeper understanding of themselves and the world around them. Key components include mindfulness practices, gratitude exercises, and happiness focused activities to promote well-being, alongside dialectical discussions and portfolio dialogues to foster critical thinking and self-awareness. This pedagogical approach not only claims to enhance academic achievement but also personal development and emotional health with more fulfilling and engaged learning for students. Teachers training, potential conflicts in discussions and subjectivity of an individual's experiences are acknowledged challenges. However, it is believed that this innovative approach has the potential to revolutionize education by creating a learning environment that is academically rigorous and supportive to students. The study concludes with a call for further exploration and implementation of this pedagogy in diverse educational settings.